Teachers' Perceptions of Creativity in the Classroom. Issue 2 (3rd April 2018) - Kettler, Todd; Lamb, Kristen N.; Willerson, Amy; Mullet, Dianna R.
Abstract : Teachers' implicit understandings of creativity may not align with current research-based understanding of creativity and characteristics associated with creative students. Even teachers who say they value creativity may actually find creative characteristics undesirable. Participating teachers ( n = 371) rated student characteristics on a scale of very undesirable to very desirable . Participants also completed a brief self-assessment of personal creativity and rank-ordered a set of educational objectives based on what they perceived as most important. Results indicated that teachers found student characteristics associated with creativity less desirable than those characteristics contraindicative to creativity ( d = 2.70). No effects were found based on the grade level ( d = 0.07) and small effects were found for subjects taught (η 2 = 0.023). Similarly, no effects were found for the teachers' level of experience (η 2 = 0.004) or age (η 2 = 0.002). Teachers' level of personal creativity was related ( r = .248) to how desirable they rated student characteristics associated with creativity, but the importance with which teachers ranked creative thinking had small effects (η 2 = 0.04) on how desirable they found characteristics associated with creativity. These results generally confirm previous studies and suggest that teachers' grade level, subject, experience, and age have no effect on their perception of creative characteristics. However, some evidence suggests that teachers who are more creative find student characteristics associated with creativity more desirable in class.